CREATION OF THE METHODOLOGY OF STATIC BALANCING OF CANTILEVER BARS FOR DRILLING DEAF HOLES IN THE DESIGN PROCESS WITH THE ANALYSIS OF MOVEMENT KINEMATICS - HOROKHOVSKYI, VIKTOR; HORDIEIEV, ANATOLYI (Herald of Khmelnytskyi National University. Technical sciences, 2025)
A methodology for determining counterweight parameters for static balancing of cantilever drill rods at the design stage is proposed, and the dynamics of rotary motion of the drill rod in SolidWorks Motion is investigated. CAD systems build a 3D model of a borscht on a scale of 1:1 in the CAD system software and, using the CAD system option, determine its mass and the coordinates of the center of gravity in three-dimensional space, create graphic projections of the borscht in the CAD system, and determine the distances using the sizing option the location of the center of gravity, the angle of rotation from the horizontal plane and calculate the mass of the counterweight, the parameters of the shape of the counterweight and build its 3D geometric configuration based on the mass, using the CAD option - the counterweight system is installed on the bar with further verification of the coordinates of the center of gravity of the bar with the counterweight using the option CAD - systems. An important aspect of the performance of the designed construction of the borscht is the analysis of the kinematics of the movement of the extreme point of the cutter during the operation of the machine. According to the results of the studies of the displacement of the tip of the boring bar cutter, it is possible to recommend rational modes of processing the workpiece when boring blind holes. Based on the tolerance for radial runout of the hole surface, the following cutting modes can be recommended for the boring bar that was studied: V = from 240 to 480 m/min. The application of the proposed methodology for determining the counterweight parameters for static balancing of the cantilever rod and the dynamics of the movement of the tip of the cutter when boring blind holes using the SolidWorks Motion software product makes it possible to reduce the time spent on performing on-site determination of the mass characteristics of the counterweight and to increase the accuracy of calculations of the distance of the center of gravity in the vertical and horizontal projection of the borscht for its specific size.